Nilai-Nilai Kultural dalam Pakaian Adat Perempuan Pada Masyarakat Melayu di Kawasan Seberang Kota Jambi Kajian Etnolinguistik - Firliyana, Nur; Afria, Rengki; Fardinal, Fardinal (Titian: Jurnal Ilmu Humaniora, 2023)
Traditional clothing is a cultural value of society. Clothing is the most obvious expression of one's identity. In accordance with the objectives of this study to describe the cultural values and meanings in the traditional clothing of Seberang Malay women in Jambi City, Jambi Province. The method in this research is descriptive qualitative using ethnolinguistic and lexicological approaches. Data and data sources in the study were obtained from interviews, recordings, and notes from informants. The results of this study obtained 8 lexicons that appear in the traditional clothing of Seberang Malay women in Jambi City.Â  For cultural meaning, 7 lexicons were obtained, consisting of 4 lexicons of cultural meaning in clothing and accessories, namely tengkuluk, bekerobong, kain duo, tudung lingkup, baju kurung, songket. There are 3 cultural meanings in the motifs used, such as the Duren Pecah, Angso Duo, and kaal Sanggat motifs. Cultural values in traditional clothing for Malay women in Jambi Kota Seberang; a) religious value, b) harmony value, c) beauty value, d) modesty value, e) art and creativity value, f) customary value, g) prosperity value, h) social value, i) tolerance value, j) respect for nature, k) philosophy Abstrak Pakaian adat merupakan suatu nilai budaya masyarakat. Pakaian merupakan ekspresi identitas seseorang yang paling jelas terlihat. Sesuai dengan tujuan dari penelitian ini untuk mendeskrisikan nilai dan makna kultural dalam pakaian adat perempuan Melayu Seberang Kota Jambi, Provinsi Jambi. Metode dalam penelitian ini adalah deskriptif kualitatif dengan menggunakan pendekatan etnolinguitk dan leksikologi. Data dan sumber data dalam penelitian diperoleh dari wawancara, rekaman, dan pencatatan yang berasal dari informan. Hasil dari penelitian ini didapatkan 8 leksikon yang muncul dalam pakaian adat perempuan Melayu Seberang Kota Jambi.Â  Untuk makna kultural didapatkan 7 leksikon, yang terdiri 4 leksikon makna kultural dalam pakaian dan aksesoris yaitu tengkuluk, bekerobong, kain duo, tudung lingkup, baju kurung, songket. Terdapat 3 makna kultural pada motif kain yang digunakan, seperti motif Duren Pecah, Angso Duo, dan Kapal Sanggat. nilai-nilai kultural dalam pakaian adat Perempuan melayu di Jambi Kota Seberang; a) nilai keagamaan, b) nilai keselarasan, c) nilai kecantikan, d) nilai kesopanan, e) nilai seni dan kreatifitas, f) nilai adat, g) nilai kemakmuran, h) nilai social, i) nilai toleransi, j) nilai penghormatan kepada alam k) nilai filosofis.